Mobile Game Technologies and Cognitive Development in Ukrainian Preschool and Primary Education: A Correlational Study - Bakhmat, Nataliia; Zahorodnia, Liudmyla; Brushnevska, Iryna; Ribtsun, Yuliia; Valentieva, Tatyana (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The current development of preschool and primary education requires the involvement of various modern technologies, among which mobile game technologies play a significant role. The purpose of this study is to determine the relationship between the use of mobile game technologies in education and the development of cognitive abilities. Purposive sampling was used to involve children (n = 58), teachers (n = 41), and parents (n = 76). The study covers children aged 5–10 years who study in preschool and primary schools in Ukraine. Several instruments were used in the study. The survey was conducted among parents and teachers. Testing, such as the Benton Visual Retention Test (BVRT) and Raven’s Progressive Matrices (RPM), is used among children. The Wechsler Intelligence Scale for Children was also used. The results show that mobile game technologies are used in educational institutions daily or several times a week. The tests showed that older children who use mobile gaming technologies have higher results in both tests. The conclusions suggest a relationship between the frequency of mobile gaming technology use and cognitive skills, with a strong positive effect on general intelligence (IQ), verbal skills (VCI), logical thinking (PRI), working memory (WMI), and information processing speed (PSI).